An assessment of the effects of an inflationary environment on health insurance performance: A Case of Premier Service Medical Aid Society - Mudokwani, V. (BUSE, 2023)
The purpose of this section is to provide a summary of the entire research. The study was based on four objectives that were meant to establish the impact of hyperinflation on the creation customer relationships, financial stability, health insurance coverage and strategies to mitigate the effects of a hyper-inflationary environment. The research was guided by the theory of dynamic capabilities. Extant literature indicated that an inflation environment had disruptive effects on business activities across different economic jurisdictions and sectors of the economy and industry. The study followed the dictates of a pragmatic research philosophy which permitted for the inclusion of both the qualitative and quantitative aspects. The research population was composed of employees at PSMAS. A sample size of 184 was selected from a unit of analysis of 340. Data was collected using a questionnaire. The main research findings indicated that hyperinflation has significantly impacted the affordability, availability, and comprehensiveness of health insurance, causing difficulties for customers in maintaining their policies and affecting the stability and reliability of health insurance providers. A hyperinflationary environment was found to negatively impacted health insurance providers’ financial stability, solvency, quality of medical insurance, reserve maintenance, capitalization, cost forecasting, and premium setting, resulting in difficulties in providing quality insurance and managing finances. This study highlighted that hyperinflation has significantly altered insurance coverage, affecting specific services and treatments, and limiting the benefits offered by insurance policies, particularly in specialized healthcare services that may not be fully covered by insurance. Even though initiatives have been made towards mitigating the effects of hyperinflation on health insurance, the full impact of these mitigatory strategies is yet to be fully explored. The recommendations for PSMAS to manage hyperinflation include negotiating long-term contracts, diversifying suppliers, implementing cost-effective measures, open communication, supplier performance monitoring, and collaboration with government entities. They also suggest investing in assets, minimizing expenses, and implementing cost management, membership growth, emergency reserves, and cost-sharing mechanisms.
Keywords: hyper-inflation; health insurance; PSMAS